Academic Performance of New Jersey's Public Schools - Wainer, Howard (Education Policy Analysis Archives, 1994)
Data from the 1992 National Assessment of Educational Progress are used to compare the performance of New Jersey public school children with those from other participating states. The comparisons are made with the raw means scores and after standardizing all state scores to a common (National U.S.) demographic mixture. It is argued that for most plausible questions about the performance of public schools the standardized scores are more useful. Also, it is shown that if New Jersey is viewed as an independent nation, its students finished sixth among all the nations participating in the 1991 International Mathematics Assessment.